Netflix’s No-censorship Policy in Subtitling Taboo Language from English into Arabic - Alsharhan, Alanoud (Journal of Audiovisual Translation, 2020)
This paper aims at examining the Arabic subtitles currently used in Netflix, particularly in instances that include taboo language. Because Netflix has a no-censorship policy, identifying the different subtitling strategies that translators working for Netflix have applied, as well as determining whether they are different from those identified as the norm in subtitling taboo language into Arabic, such as omission and euphemism are important questions to be answered in this study. Subtitling strategies applied are identified and analysed while the current subtitling strategies for extralinguistic cultural references (ECRs) are used as a starting point to establish a new, modified taxonomy that represents subtitling taboo language in the two languages and cultures under analysis. The data suggest that two prominent modifications of the current subtitling strategies are needed, which are euphemism and shift in register. The audiovisual material examined in this study consists of five Netflix programs from different genres, in which taboo content and language are abundant. The subtitles of these shows are extracted in order to compile a small parallel corpus to be analysed both qualitatively and quantitively. The results indicate that a variety of subtitling strategies are used to render taboo language into Arabic on Netflix shows, which is different from previous norms that commonly used omission and other forms of euphemising taboo language. Another important result is that nearly half of the taboo language instances are still euphemised despite the no-censorship policy.